The influence of Employee Well being, Job Satisfaction anda Transformasional Leadership on Employee Performance of HR Division at PT Perkebunan Nusantara I Regional 4 Surabaya - Tita, Sephia Dwi Titania; Tri Andjarwati (Nirta Learning Centre, 2024)
This study aims to determine the effect of employee well-being, job satisfaction and transformational leadership on employee performance. The method used in this study is a quantitative approach with data collection through questionnaires distributed to 60 employees. The instrument test in this study is a validity test and a reliability test. The data analysis used is multiple linear regression analysis with hypothesis testing using the t/partial test and the coefficient of determination (R2). The data was tested and analyzed through the Statistical Package for the Social Sciences (SPSS). The results of the study showed that all indicators were valid and reliable. The results of the t test showed that employee well-being had a positive and significant effect on employee performance. job satisfaction has a positive and significant effect on employee performance. Transformational leadership has a positive and significant effect on employee performance. the result of the determination coefficient test of 0.586 means that 58.6% of Employee Performance at PT Perkebunan Nusantara I Regional 4 Surabaya is influenced by employee well being, job satisfaction and transformational leadership factors. While the remaining 41.4% is influenced by other factors that are not influenced by this variable.